1981
DOI: 10.1037/0022-0663.73.3.419
|View full text |Cite
|
Sign up to set email alerts
|

How do young adults read directions with and without pictures?

Abstract: (Continue on reverse aide if necessary and Identify by ilack mmtber)his research is designed to explore the manner in which people read and use procedural information (directions) presented to them in text and illustra tions.University undergraduates read directions for the assembly of a model loading cart, assembling the model as they read. The use of illustrations with text was found to produce significantly more accurate performance of the task. Results also suggest that specific types of information are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1
10

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 12 publications
(10 reference statements)
7
37
1
10
Order By: Relevance
“…These results corroborate previous studies (Bieger & Glock, 1984-85;Booher, 1975;Braby, et al, 1982;Garnier et al, 2000); Heiser et al, 2004;Lowe & Pramono, 2006;Stone & Glock, 1981), which suggest that text format was the least effective method to convey information for novel procedural tasks, such as assembling and operating a novel object. They also confirm the multimedia principle, which purports that instructions that contain words and pictures facilitate better instructions evidenced by superior performance in conditions that had at least one picture in both assembly and operation tasks compared to words alone (Fletcher & Tobias, 2005;Mayer 2005b).…”
Section: Pictures and Arrows As Information For Actionssupporting
confidence: 82%
See 1 more Smart Citation
“…These results corroborate previous studies (Bieger & Glock, 1984-85;Booher, 1975;Braby, et al, 1982;Garnier et al, 2000); Heiser et al, 2004;Lowe & Pramono, 2006;Stone & Glock, 1981), which suggest that text format was the least effective method to convey information for novel procedural tasks, such as assembling and operating a novel object. They also confirm the multimedia principle, which purports that instructions that contain words and pictures facilitate better instructions evidenced by superior performance in conditions that had at least one picture in both assembly and operation tasks compared to words alone (Fletcher & Tobias, 2005;Mayer 2005b).…”
Section: Pictures and Arrows As Information For Actionssupporting
confidence: 82%
“…Participants' behaviours were the dependent variables for the study, A task analysis of the assembly and operating procedure was conducted by observing and recording the procedures performed by a technician on the design team and the designer. Instructions were developed from the task analysis and the aid of existing guidelines (Bieger & Glock, 1984-85;Booher, 1975;Braby, Kincaid, & McDaniel, 1982;Dixon, 1982;Hegarty, 1992;Hodgkinson & Hughes, 1982;Horton, 1994;Krull & Sharp, 2006;Kurata & Egenhofer, 2005;Nailen, 1981;Resnick, 1976;Stone & Glock, 1981;Szlichcinski, 1979;Tversky, et al, 2000). Six different instruction manuals were produced to coincide with the six experimental conditions in the study Appendix 1 shows an example of the text format in the first six pages of the manuals.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies showed no clear result pattern regarding the preferred order of information extraction. Whereas Hegarty and Just (1993) showed that participants looked first at the verbal information, other studies found initial processing of the pictorial information (Rayner, Rotello, Steward, Keir, & Duffy, 2001;Underwood, Jebbett, & Roberts, 2004;Stone & Glock, 1981) suggesting different (task-dependent) strategies.…”
Section: Processing Of Visual Informationmentioning
confidence: 99%
“…Mayer's (1997) theory posits that the simultaneous processing of texts and images, and active selection of components from these presentations, are the two primary contributors to multimedia learning advantages. This theory has received repeated empirical supported in the context of both educational (Stone & Glock, 1981;Peeck & Jans, 1987;Mayer, 1989;Mayer & Gallini, 1990;Glenberg & Langston, 1992;Mayer et al, 1996) and cognitive psychology (Gyselinck & Tardieu, 1994;Gyselinck et al, 2002;Brunyé et al, 2006).…”
Section: Multimedia Design Principles and Working Memorymentioning
confidence: 99%
“…While the majority of multimedia research examines the learning effectiveness of complementing texts with images, the converse is relatively under-researched (Stone & Glock, 1981;Gyselinck, 2002;Brunyé et al, 2006); that is, complementing stand-alone images with text, such as commonly seen when labels or short descriptions are placed on maps. Thus, the cognitive impact of systematic variation in labeling and/or graphic detail on maps (or in spatial descriptions) has not been determined.…”
Section: Multimedia Design Principles and Working Memorymentioning
confidence: 99%